2019
DOI: 10.1111/jgs.16224
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential Acetylcholinesterase Inhibitor‐Induced Rhinorrhea Prescribing Cascade

Abstract: To the Editor: The most commonly used medications for patients with dementia are acetylcholinesterase inhibitors (AChEIs; donepezil, rivastigmine, galantamine). 1 Use of these medications are often limited by adverse events (AEs) including nausea, vomiting, diarrhea, incontinence, hypersalivation, sweating, lacrimation, rhinorrhea, and bronchorrhea. 1-3 In particular, rhinorrhea is not a well-recognized AE of AChEI and was only previously documented in a meta-analysis of randomized controlled trials of donep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The rhinorrhea medications consist of antihistamine, nasal anticholinergics and nasal glucocorticoids. 178 These co-medications may contribute to negative side effects. Therefore, physicians should consider dose reduction of AChEIs instead of adding other medications to treat adverse effects of AChEIs.…”
Section: Uncommon Adverse Effectsmentioning
confidence: 99%
“…The rhinorrhea medications consist of antihistamine, nasal anticholinergics and nasal glucocorticoids. 178 These co-medications may contribute to negative side effects. Therefore, physicians should consider dose reduction of AChEIs instead of adding other medications to treat adverse effects of AChEIs.…”
Section: Uncommon Adverse Effectsmentioning
confidence: 99%
“…Figure 1 shows that of 103 articles included in our previous systematic review, 18 three used the same database to investigate a single prescribing cascade at different points in time, 24–26 of which we only selected the most recent 26 . Six further studies only reported exploratory studies, 27–32 five only reported cross‐sectional studies, 5,33–36 and nine articles did not find any significant positive associations between index and marker drugs 37–45 . The remaining 81 articles reported 99 prescribing cascades (i.e., distinct combinations of index and marker drugs).…”
Section: Resultsmentioning
confidence: 99%
“…The prescribing cascade was defined as existing when an adverse drug event (ADE) was misinterpreted as a new medical condition that resulted in a new medication being prescribed to treat the ADE ( Rochon and Gurwitz, 1995 ; Rochon and Gurwitz, 2017 ; McCarthy et al, 2019 ). Prescribing cascades can affect people of any age ( Gill et al, 2005 ; Vouri et al, 2018 ; Huh et al, 2019 ; Vouri et al, 2020 ) but have been found to occur more frequently in older adults ( Rochon and Gurwitz, 2017 ; McCarthy et al, 2019 ). This is due in part to increased polypharmacy among older compared to younger adults which increases exposure to drugs that potentially initiate the prescribing cascade ( Beijer and de Blaey, 2002 ; Canadian Institute for Health Information, 2018 ).…”
Section: Introductionmentioning
confidence: 99%